2017
DOI: 10.1038/s41598-017-17600-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Erasin: a chromone-based STAT3 inhibitor which induces apoptosis in Erlotinib-resistant lung cancer cells

Abstract: Inhibition of protein-protein interactions by small molecules offers tremendous opportunities for basic research and drug development. One of the fundamental challenges of this research field is the broad lack of available lead structures from nature. Here, we demonstrate that modifications of a chromone-based inhibitor of the Src homology 2 (SH2) domain of the transcription factor STAT5 confer inhibitory activity against STAT3. The binding mode of the most potent STAT3 inhibitor Erasin was analyzed by the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
15
1
Order By: Relevance
“…It thereby inhibits receptor autophosphorylation and blocks downstream signals 16 . Erlotinib is used in treatment of different types of cancer as lung cancer 17 and head and neck squamous cell carcinoma 18 . Many studies showed beneficial effects of erlotinib in different kidney injuries.…”
mentioning
confidence: 99%
“…It thereby inhibits receptor autophosphorylation and blocks downstream signals 16 . Erlotinib is used in treatment of different types of cancer as lung cancer 17 and head and neck squamous cell carcinoma 18 . Many studies showed beneficial effects of erlotinib in different kidney injuries.…”
mentioning
confidence: 99%
“…Previous study has shown that STAT3 dimerization is blocked and complex formation of STAT3 is impaired by Toosendanin, a triterpenoid saponin compound, which can inhibit osteosarcoma growth and metastasis ( Zhang et al, 2017 ). In addition, other study has reported that Erasin promotes apoptosis in Erlotinib-resistant lung cancer cells by direct inhibition of tyrosine phosphorylation of STAT3 ( Lis et al, 2017 ). Moreover, a recent study has demonstrated that S3I-201.1066, a novel small-molecule, binds with a high affinity to STAT3, disrupts STAT3 activation and function, and thereby increases anti-breast cancer activity in vitro and in vivo ( Zhang et al, 2010 ; Yeh and Frank, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence polarization assays were performed at approximately 37 • C, as described previously [77]. The final concentration of buffer components used for all fluorescence polarization (FP) assays was 10 mM HEPES (pH7.5), 1mM EDTA, 0.1% Nonidet P-40, 50mM NaCl, and 10% DMSO.…”
Section: Fluorescence Polarization Assaysmentioning
confidence: 99%